"Frame Wobbling" Causing Crustal Deformation Around the Ordos Block. Issue 1 (11th January 2021) - Hao, Ming; Wang, Qingliang; Zhang, Peizhen; Li, Zhangjun; Li, Yuhang; Zhuang, Wenquan
Abstract: An accurate and dense GPS velocity field across the Ordos block is presented based on extensive observations. We utilized velocities from evenly distributed GPS stations within the block to estimate the parameters of rigid block motion and internal strain. Our results indicate that the Ordos block behaves rigidly, with a negligible anticlockwise rotation. The velocity profiles, strain, and block motion suggest that: the interior of the block undergoes no differential motion and internal strain is insignificant; relative to the Ordos, the adjacent blocks move in different directions and at different rates, and exert varying forces on it; the adjacent blocks deform the Ordos block along its boundaries of grabens and fold‐thrust fault zones. The Ordos block accommodates the forces exerted by the adjacent blocks through strain and deformation across its boundaries, which should be high strain or strain gradient zones. This pattern of deformation is illustrated by frame wobbling. Plain Language Summary: The Ordos block connects the Tibetan Plateau and North China plain and experiences complex tectonic movements. The interior of the Ordos block has insignificant seismic activity and differential movements, but its surrounding grabens and active faults undergo intense seismic activity and deformation. Investigating the deformation of the Ordos block is essential for deciphering the interactions between active tectonic blocks, determining the mechanisms of large earthquakes, and understanding the dynamics of continental deformation. In this study, a dense GPS velocity field in and around the Ordos block was used to determine the kinematics of the Ordos block. Our results indicate that the Ordos block behaves rigidly, with negligible anticlockwise rotation. The deformation pattern of the Ordos block is illustrated by the "frame wobbling" model, wherein the deformation or strain is located along the peripheral boundaries of the block, while little strain is located in its interior. The forces that cause this "frame wobbling" come from the movements of the adjacent blocks with respect to the Ordos block. This "frame wobbling" deformation style may be typical for intracontinental deformation. Key Points: A dense GPS velocity field for the Ordos block and the surrounding region is presented The rigid block motion of the Ordos block behaves as a negligible anticlockwise rotation Contemporary kinematics of the Ordos block can be interpreted as "frame wobbling" deformation